1997
DOI: 10.1007/s004150050121
|View full text |Cite
|
Sign up to set email alerts
|

Human herpes virus 6 and human herpes virus 8 DNA sequences in brains of multiple sclerosis patients, normal adults and children

Abstract: In order to determine whether the newly discovered human herpesviruses (HHVs) are involved in multiple sclerosis (MS), we investigated by polymerase chain reaction the presence of specific deoxyribonucleic acid (DNA) sequences belonging to human herpesvirus 6 (HHV-6) and to human herpesvirus 8 (HHV-8), in the peripheral blood mononuclear cells (PBMCs), and in the brain and spinal cord plaques from MS patients. Normal adult and stillborn children's brains were investigated as controls. PBMCs from 56 MS patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 24 publications
6
50
2
Order By: Relevance
“…Among them, HHV-6 appears to be one of the most serious candidates in the category of infectious triggers, on the basis of immunological, virological, and experimental data (6). These data include the isolation of this virus from diseased CNS tissues of MS patients, serologic studies of HHV-6 antibody reactivity in their sera and CSF, and in situ detection of HHV-6 DNA transcripts (141,183,(185)(186)(187)(188). This hypothesis also results from general considerations founded on the neurotropism of the virus combined with its theoretical capacity to induce both neuroinflammation and autoimmunity.…”
Section: Chronic Infectionsmentioning
confidence: 99%
“…Among them, HHV-6 appears to be one of the most serious candidates in the category of infectious triggers, on the basis of immunological, virological, and experimental data (6). These data include the isolation of this virus from diseased CNS tissues of MS patients, serologic studies of HHV-6 antibody reactivity in their sera and CSF, and in situ detection of HHV-6 DNA transcripts (141,183,(185)(186)(187)(188). This hypothesis also results from general considerations founded on the neurotropism of the virus combined with its theoretical capacity to induce both neuroinflammation and autoimmunity.…”
Section: Chronic Infectionsmentioning
confidence: 99%
“…More recent studies demonstrated higher titers of antibodies to HHV-6 and cell-free DNA of HHV-6 in serum and cerebrospinal fluid (CSF) of MS patients, suggesting reactivation of HHV-6 in MS (1-2, 4, 20-23, 29, 35-37, 46, 50). However, other investigators found no differences in these measurements between MS patients and control subjects, failing to confirm such an association (6,14,24,26,28,30,41). It is important to note that the assays reported in some of these studies were based on the whole HHV-6 virus, which contains viral protein components sharing extensive amino-acid-sequence homology with other related viral proteins, such as CMV and HHV-7, thus making the results difficult to interpret.…”
mentioning
confidence: 93%
“…However, other reports have failed to detect serologic (Nielsen et al, 1997) or virologic (Sanders et al, 1996;Martin et al, 1997;Merelli et al, 1997) evidence of an association between HHV-6 and MS. As such, de®nitive proof of a role for HHV-6 in the pathogenesis of MS awaits further study.…”
Section: Multiple Sclerosismentioning
confidence: 92%